Programmed Intermittent Epidural Bolus vs. Patient-controlled Epidural Analgesia for Maintenance of Labour Analgesia: A 2-Center, Double-blind, Randomized Study. Issue 4 (22nd December 2021) - Roofthooft, E.; Barbé, A.; Schildermans, J.; Cromheecke, S.; Devroe, S.; Fieuws, S.; Rex, S.; Wong, C.A.; Van de Velde, M.
Abstract : ( Anaesthesia . 2020;75:1635–1642) Many institutions use patient-controlled epidural analgesia (PCEA) for pain relief during labor; however, programmed intermittent epidural bolus+PCEA (PIEB) has emerged as possibly superior to PCEA alone. PIEB has been found to provide pain relief with less local anesthetic, fewer or later patient-administered boluses and less motor block than PCEA strategies. PIEB has also been shown to reduce the need for instrumental vaginal delivery and manual bolus intervention by the anesthetist, and to improve maternal satisfaction. To date, there are no known studies comparing PIEB with PCEA without background infusion. The aim of this study is to compare the incidence of breakthrough pain with PIEB and PCEA.